2022 IEEE 19th International Symposium on Biomedical Imaging (ISBI) 2022
DOI: 10.1109/isbi52829.2022.9761411
|View full text |Cite
|
Sign up to set email alerts
|

Towards Measuring Domain Shift in Histopathological Stain Translation in an Unsupervised Manner

Abstract: Domain shift in digital histopathology can occur when different stains or scanners are used, during stain translation, etc. A deep neural network trained on source data may not generalise well to data that has undergone some domain shift. An important step towards being robust to domain shift is the ability to detect and measure it. This article demonstrates that the PixelCNN and domain shift metric can be used to detect and quantify domain shift in digital histopathology, and they demonstrate a strong correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In [132], Aubreville et al showed that the influence of the color domain shift introduced by different scanners strongly affects the performance of CNN-based mitosis detection on histological H&E slides. In [133], Nisar et al have also shown that it is possible to detect and estimate the staining shift in digital histopathology. To that aim, they considered a domain shift metric measuring the differences between two domains' distributions using features extracted from pre-trained neural networks.…”
Section: ) Influence Of Colormentioning
confidence: 99%
“…In [132], Aubreville et al showed that the influence of the color domain shift introduced by different scanners strongly affects the performance of CNN-based mitosis detection on histological H&E slides. In [133], Nisar et al have also shown that it is possible to detect and estimate the staining shift in digital histopathology. To that aim, they considered a domain shift metric measuring the differences between two domains' distributions using features extracted from pre-trained neural networks.…”
Section: ) Influence Of Colormentioning
confidence: 99%